EVOLUTION OF STATE FAMILY POLICY IN RUSSIA FROM SOVIET TIMES TO THE PRESENT - A. V. Noskova (Vestnik MGIMO-Universiteta, 2013)
The paper describes some peculiarities in evolution of the State family politics and policies in Russia since the beginning of the XX century to present time. The aim of the paper is to shed light on the family state policy in Russia during the different periods of time. We define here the family state policy widely enough as the various state activity (ideological, legislative, economic, social) concerning institute of family. The analysis of the state measures concerning the family in different social and political contexts allowed us to allocate the five main stages and models of the family state policy in Russia. They are: the post-revolutionary model (1917-1926), the «Stalin» model (1927-1953), the "welfare" Soviet model (1954-1991), the yearly post- Soviet model (1991-2005), the modern model (since 2006). The paper is based on the some demographic and sociological surveys data and devoted to an analysis of the family changes in these various periods. On the one hand, the family policies were a reaction to new social requirements and demographic changes (decline of fertility, for example). On the other hand, the state activity concerning a family itself caused transitions in the family institute. We show how various measures of soviet and post-soviet family policies and public interventions in family life have influenced on the family relations.